INCIDENCE OF LEAF AND FRUIT EATER, Diaphania indica (Saunders) IN MELON AT SRI KUNCORO VILLAGE, PONDOK KELAPA SUBDISTRICT, BENGKULU TENGAH REGENCY - Nadrawati Nadrawati; Agustin Zarkani; Priyatiningsih Priyatiningsih; Aprilian Pitoyo (BPFP Universitas Bengkulu, 2023)
Melon is a fruit plant that has the potential to be developed and can become a superior horticultural product. The demand for melons continuously increases yearly, requiring a large and continuous supply. Fruit must be available at any time in sufficient quantity and quality to be used as an agricultural commodity with high economic value. Diaphania indica (Lepidoptera: Crambidae) is a significant pest that attacks the leaves and fruit of the Cucurbitaceae family, including economically important crops such as melon. Studies on Diaphania pests that attack melon leaves and fruit have not been widely studied in Indonesia. Also, due to the cases happening of leaf and fruit-eating attacks in Bengkulu, proper pest control efforts are needed. One of the basics for determining how to control is to know the population density and the level of damage caused by these pests. This research was conducted on the farmers' land in Sri Kuncoro Village, Pondok Kelapa Sub-District, Bengkulu Tengah Regency, November 2021-January 2022. The variables observed were the population density of D. indica, the percentage of leaf damage, and the percentage of parasitic larvae. The results showed variations in the density of D. indica larvae and the percentage of leaf damage. The mean population density of larvae was 1.47 per plant, and the percentage of infected leaves was 29.49%. Parasitoids associated with D. indica larvae were found in Apanteles spp, with a percentage of parasitized D. indica larvae of 46.67%.